The effect of work stress on the performance of employees psychological well-being and subjective well-being (Study at PT. Global Insight Utama Bali area) - Tsalasah, Ekromi Fraida; Noermijati, Noermijati; Ratnawati, Kusuma (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2019)
This study aimed to analyze the effect of work stress on employee performance, analyze the effect of work stress on psychologicall well-being, to analyze the influence of psychologicall well-being of the employee's performance, analyze the effect of work stress on subjective well-being, to analyze the influence of subjective well-being of the performance employee, psychologicall To analyze the effect of well-being as mediation work stress on employee performance, and analyze the influence of subjective well-being as mediation work stress on employee performance. Mechanical analysis using PLS. The analysis showed that the effect of work stress on employee performance, job stress affect the well-being psychologicall, psychologicall well-being affect the performance of the employee